1970
DOI: 10.1080/00140137008931141
|View full text |Cite
|
Sign up to set email alerts
|

Critical Time Intervals for Taking in Flight Information in a Ball-Catching Task

Abstract: A ball-catching task in which the ball was caused to enter on a parabolic flight path by means of a mechanical apparatus was administered to 36 male students between the ages of 18 and 40 years. An electronic device enabled the ball to be illuminated for predetermined temporal intervals during its flight. Results indicated that in this relatively unpredictable task opportunity to watch the ball for longer periods of time resulted in increased catching success. Results are discussed in relation to previous expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 12 publications
3
33
0
2
Order By: Relevance
“…(2) Brief targetviewing times: It is apparent from the performance of different lAs that people can reliably achieve a temporal precision of within 10 msec when the target is visible for only a few hundred milliseconds (e.g., Bootsma & van Wieringen, 1990;McLeod et a!., 1985;Regan, 1992;Tresilian, 1994a). A comparable precision can be achieved with viewing times ofless than about 100 msec (Sharp & Whiting, 1975;Whiting, Gill, & Stephenson, 1970). In addition, there is the possibility of controlling movements in an on-going fashion using TTC information available during execution (e.g., Lee, Young, Reddish, Lough, & Clayton, 1983) and the possibility that execution times are determined by the TTC at initiation, when the action is too brief to admit on-going control (Bootsma, 1989;Tresilian, 1994c).…”
Section: Direct Perception-action Couplingmentioning
confidence: 95%
“…(2) Brief targetviewing times: It is apparent from the performance of different lAs that people can reliably achieve a temporal precision of within 10 msec when the target is visible for only a few hundred milliseconds (e.g., Bootsma & van Wieringen, 1990;McLeod et a!., 1985;Regan, 1992;Tresilian, 1994a). A comparable precision can be achieved with viewing times ofless than about 100 msec (Sharp & Whiting, 1975;Whiting, Gill, & Stephenson, 1970). In addition, there is the possibility of controlling movements in an on-going fashion using TTC information available during execution (e.g., Lee, Young, Reddish, Lough, & Clayton, 1983) and the possibility that execution times are determined by the TTC at initiation, when the action is too brief to admit on-going control (Bootsma, 1989;Tresilian, 1994c).…”
Section: Direct Perception-action Couplingmentioning
confidence: 95%
“…The human perceptuo-motor system has been shown to adapt to information-based perturbations in a variety of tasks, including repetitive (Woodworth 1899;Vince 1948) and discrete aiming tasks (Keele and Posner 1968;Carlton 1981;Moore 1984;Elliott 1988;, grasping (Wing et al 1986;Winges et al 2003;Fukui and Inui 2006), catching (Whiting et al 1970(Whiting et al , 1973Whiting and Sharp 1974;Whiting 1974, 1975;Lamb and Burwitz 1988;Lacquaniti and Maioli 1989;Mazyn et al 2007b;Dessing et al 2009) and hitting (Marinovic et al 2009;van Soest et al 2010). Imposing such perturbations in experimental settings influences factors such as movement preparation, as well as underlying control processes that are responsible for adaptations in kinematics as the movement unfolds (Elliott and Lee 1995;van der Kamp et al 1997;Schenk et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies on interceptive actions have found maximal performance to occur only under full visibility conditions (Sharp, 1975;Whiting, Gill, & Stephenson, 1970). Thus, although successful performance is in fact possible on the basis of only limited time spans of visual information, performance under such conditions never equals that of the normal situation of continuously available information.…”
mentioning
confidence: 99%